An MDT-based rapid assessment method for the spatial distribution of trafficable sections of roads hit by earthquake-induced landslides - Bai, Xianfu; Dai, Yuqian; Zhou, Qingyun; Yang, Zhiquan (Frontiers in Earth Science, 2023)
In mountainous areas, roads are often damaged by earthquake-induced landslides (EL). The degree of road damage and the existing functional state will have a very important impact on the whole earthquake relief work. However, this question has long been plaguing scientists engaged in the risk assessment. Now, an MDT-based rapid assessment method for the spatial distribution of trafficable sections of roads (TSR) hit by EL is proposed. The method mainly consists of three procedures: 1) Demarcate the road sections in the evaluated region; 2) Create the data for earthquake-induced landslide sensitivity level for the evaluated region; 3) Use the sample data to devise the MDT model for the TSR hit by EL and calculate the trafficability of road sections. This method was applied in the study of the 2008 Wenchuan Ms 8.0, the 2014 Ludian Ms 6.5, the 2012 Yiliang Ms 5.6 and Ms 5.7 earthquake-stricken regions. The case of Wenchuan earthquake was adopted to establish the method. The cares of Ludian and Yiliang were used to evaluate whether the method could be transplanted into similar regions. The p-value and the kappa coefficient were used to test and evaluate the significance and the consistence of the actual situation. Our results suggest: ⅰ) The Wenchuan evaluated region had the p-value 2.52 × 10−203 and the kappa coefficient 0.91. Less than 1% of the road sections that were inferred to be trafficable with the established method were actually interrupted by EL. The interruptions in the road sections that were inferred to be un-trafficable were 12 times of those in the other road sections. ⅱ) The Ludian and Yiliang earthquake-stricken regions had the p-value 9.7 × 10−107 and the kappa coefficient 0.81. Only 1.31% of the road sections that were trafficable according to the calculation results of the model had been actually interrupted by EL. The interruptions caused by EL in the un-trafficable road sections according to the calculation results were 5.2 times of those in the trafficable road sections. This method could be applied in other similar regions when a certain error was permitted.